2013
DOI: 10.1016/j.tree.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic or mystic? Glacial tree refugia in northern Europe

Abstract: Here, we examine the evidence for tree refugia in northern Europe during the Late Pleniglacial (LPG) interval of maximum tree-range contraction. Our review highlights the often equivocal nature of genetic data and a tendency to overestimate potential tree distributions due to warm climate-model bias, and also reveals a convergence of macrofossil and pollen evidence. What emerges is the absence of temperate trees north of 45°N and a west-east (W-E) asymmetry in boreal tree distribution, with a treeless Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
331
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(350 citation statements)
references
References 61 publications
14
331
1
4
Order By: Relevance
“…Molecular genetic data revealed considerable divergence between populations of many arboreal species in southern refugial centres in Iberia, Italy, the Balkans and Greece. Arboreal refugia and migration paths, identified by both biogeographical, palaeobotanical and phylogeographical studies (Petit et al, 2005;Cheddadi et al, 2006;Magri et al, 2006;Liepelt et al, 2009;Médail and Diadema, 2009;Tzedakis, 2009;Tzedakis et al, 2013), sometimes confirmed the speculated locations (e.g. Bennett et al, 1991) and their link to modern biodiversity hotspots, but most mechanisms still have to be fully understood.…”
Section: Introductionmentioning
confidence: 85%
“…Molecular genetic data revealed considerable divergence between populations of many arboreal species in southern refugial centres in Iberia, Italy, the Balkans and Greece. Arboreal refugia and migration paths, identified by both biogeographical, palaeobotanical and phylogeographical studies (Petit et al, 2005;Cheddadi et al, 2006;Magri et al, 2006;Liepelt et al, 2009;Médail and Diadema, 2009;Tzedakis, 2009;Tzedakis et al, 2013), sometimes confirmed the speculated locations (e.g. Bennett et al, 1991) and their link to modern biodiversity hotspots, but most mechanisms still have to be fully understood.…”
Section: Introductionmentioning
confidence: 85%
“…A significant role in the development of the diversity of European beech was played by the areas where the migration routes from different refugia interacted during the postglacial recolonisation (Comps et al 2001;Widmer and Lexer 2001;Petit et al 2003). Moreover, the latest paleoecological and phylogeographical research indicates the former existence of potential northern refugial areas, which survived the period of glaciations due to favourable climatic-habitat conditions (Willis and van Andel 2004;Tzedakis et al 2013). So far, the role of such refugia in the analysis of the genetic variation within Europe has been underestimated (Willis and van Andel 2004;Svenning and Skov 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Small, ''cryptic'' refugia also existed in Northern Europe during glacial periods (Stewart et al 2010). However, these northern cryptic refugia allowed the persistence of a very limited number of species, and their role in determining current distribution patterns is debated (Tzedakis et al 2013;Rull 2014). Moreover, while areas in Southern European regions acted as long-term refugia, which were inhabited throughout full glacial-interglacial cycles, refugial areas in northern regions were inhabited only during the contraction phases (Stewart et al 2010).…”
Section: Discussionmentioning
confidence: 99%